Silences in NGO discourse - Shivji, Issa G. (Nairobi Fahamu, 2007)
One of the most articulate critics of the destructive effects of neoliberal policies in Africa, and in particular of the ways in which they have eroded the gains of independence, Issa Shivji shows in two extensive essays in this book that the role of NGOs in Africa cannot be understood without placing them in their political and historical context. As structural adjustment programs were imposed across Africa in the 1980s and 1990s, the international financial institutions and development agencies began giving money to NGOs for programs to minimize the more glaring inequalities perpetuated by their policies. As a result, NGOs have flourished?and played an unwitting role in consolidating the neoliberal hegemony in Africa. Shivji argues that if social policy is to be determined by citizens rather than the donors, African NGOs must become catalysts for change rather than the catechists of aid that they are today.
Includes bibliographical references (p. 48-52).
Keywords: Non-governmental organizations--Africa.